(untitled) (2016)
An antioxidant flavonoid has been isolated from methanolic leaf extract of Alchornea coelophylla Pax & K. Hoffm. by means of different column chromatography steps with DIAION HP-20 resin and silica gel in combination with analytical high-performance liquid chromatography (HPLC). It was identified as Apigenin-8-C-(α-L-rhamnopyranosyl-(1→2)-β-D-glucopyranoside) on the basis of spectroscopic analysis and by comparison with related values reported in the literature. This compound exhibited high in vitro antioxidant activity through DPPH• and ABTS•+ colorimetric assays with IC50 values of 7.528 and 379.7 μg. mL-1, respectively.